PTSD symptoms, depressive symptoms, and subjective cognitive concerns in WTC‐exposed and non‐WTC‐exposed firefighters. Issue 10 (20th August 2021) - Mueller, Alexandra K.; Singh, Ankura; Webber, Mayris P.; Hall, Charles B.; Prezant, David J.; Zeig‐Owens, Rachel
Abstract: Background: Firefighting has been associated with posttraumatic stress disorder (PTSD) and other mental health conditions. We previously found that among Fire Department of the City of New York (FDNY) responders to the World Trade Center (WTC) disaster, higher‐intensity WTC‐exposure predicted PTSD symptoms, depressive symptoms, and subjective cognitive concerns. The present study aims to compare these symptoms in the FDNY WTC‐exposed cohort versus a comparison cohort of non‐FDNY, non‐WTC‐exposed firefighters. Methods: The study population included WTC‐exposed male firefighters from FDNY ( N  = 8466) and non‐WTC‐exposed male firefighters from Chicago ( N  = 1195), Philadelphia ( N  = 770), and San Francisco ( N  = 650) fire departments who were employed on 9/11/2001 and completed a health questionnaire between 3/1/2018 and 12/31/2020. Current PTSD symptoms, depressive symptoms, and subjective cognitive concerns were assessed via validated screening instruments. Multivariable linear regression analyses stratified by fire department estimated the impact of covariates on each outcome. Results: Adjusted mean PTSD symptom scores ranged from 23.5 ± 0.6 in Chicago firefighters to 25.8 ± 0.2 in FDNY, and adjusted mean depressive symptom scores ranged from 7.3 ± 0.5 in Chicago to 9.4 ± 0.6 in Philadelphia. WTC‐exposure was associated with fewer subjective cognitive concerns ( β  = −0.69 ± 0.05, p  < .001) after controlling for covariates. Across cohorts, older age was associated with more cognitive concerns, but fewer PTSD and depressive symptoms. Conclusions: WTC‐exposed firefighters had fewer cognitive concerns compared with non‐WTC‐exposed firefighters. We were unable to estimate associations between WTC exposure and PTSD symptoms or depressive symptoms due to variability between non‐WTC‐exposed cohorts. Longitudinal follow‐up is needed to assess PTSD, depressive, and cognitive symptom trajectories in firefighter populations as they age.